1992
DOI: 10.1038/355545a0
|View full text |Cite
|
Sign up to set email alerts
|

Expansion of an unstable DNA region and phenotypic variation in myotonic dystrophy

Abstract: Myotonic dystrophy is the commonest adult form of muscular dystrophy, with an estimated incidence of 1 per 7,500, although this is likely to be an underestimate because of the difficulty of detecting minimally affected individuals. It is a multisystem autosomal dominant disorder of unknown biochemical basis. No case of new mutation has been proven. We have isolated a human genomic clone that detects novel restriction fragments specific to individuals with myotonic dystrophy. A two-allele EcoRI polymorphism is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
267
0
14

Year Published

1992
1992
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 659 publications
(284 citation statements)
references
References 17 publications
3
267
0
14
Order By: Relevance
“…The unstable expansion of CTG triplet repeats in the uncoding region of the DMPK-gene is considered to be responsible for the pathological changes associated with this disease (1)(2)(3)(4)(5). These changes are not mediated by the DMPK gene itself but by a toxic gain-of-function effect caused by the expanded CTG repeat in the mutant DMPK mRNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unstable expansion of CTG triplet repeats in the uncoding region of the DMPK-gene is considered to be responsible for the pathological changes associated with this disease (1)(2)(3)(4)(5). These changes are not mediated by the DMPK gene itself but by a toxic gain-of-function effect caused by the expanded CTG repeat in the mutant DMPK mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Myotonic dystrophy type 1 (DM1) is an autosomal dominant disorder, which is caused by the unstable expansion of a CTG trinucleotide repeat located in the 3' untranslated region of the gene encoding DM protein kinase (DMPK) on chromosome 19q13.3 (1)(2)(3)(4)(5). DM1 is characterized by myotonia, progressive muscular weakness and atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…DM is the most prevalent adult muscular dystrophy in Europe, North America, India, and North Eastern Asia, with prevalence of 0.2-9.9 per 100,000 individuals (Araki, 1976;Harper, 1989;Nakagawa et al, 1991). The mutation causing DM has been characterized as an expansion of the unstable CTG trinucleotide repeat in the 3'-untranslated region (UTR) of the DM protein kinase (DM-PK) gene located in chromosome 19q13.3 (Brook et aL, 1992;Buxton et aL, 1992;Fu et al, 1992;Harley et al, 1992a;Mahadevan et al, 1992). Statistical data on DM mutation are essential for genetic counseling.…”
Section: Introductionmentioning
confidence: 99%
“…The mutation causing DM has been identified as an expansion of an unstable trinucleotide (CTG) n repeat in almost all ethnic populations Buxton et al 1992;Fu et al 1992;Harley et al 1992;Mahadevan et al 1992). Osame and Furusho (1983) carried out the first detailed epidemiological studies in Kagoshima prefecture and suggested the possibility of a DM founder chromosome in this geographically small region of Japan.…”
Section: Introductionmentioning
confidence: 99%